Construction of ultrathin MnO2 decorated graphene/carbon nanotube nanocomposites as efficient sulfur hosts for high-performance lithium–sulfur batteries. Issue 11 (21st February 2019) - Wang, Nan; Peng, Sikan; Chen, Xiang; Wang, Jixian; Wang, Chen; Qi, Xin; Dai, Shenglong; Yan, Shaojiu
Abstract : Ultrathin MnO2 nanosheets and nano size sulfur particles distributed uniformly on the surface of G/CNT hybrids, which exhibit high rate performance and long-term cycling performance. Abstract : Lithium–sulfur batteries are attracting significant attention due to their high theoretical specific capacity and low cost. However, their applications are hindered by the poor conductivity of sulfur and capacity fading caused by the shuttle effect. Here, ultrathin manganese dioxide decorated graphene/carbon nanotube nanocomposites are designed as sulfur hosts to suppress the shuttle effect and improve the adsorption efficiency of polysulfides. The graphene/carbon nanotube hybrids, with extraordinary conductivity and large surface area, function as excellent channels for electron transfer and lithium ion diffusion. The ultrathin manganese dioxide nanosheets enable efficient chemical interaction with polysulfides and promote the redox kinetics of polysulfides. As a result, an ultrathin manganese dioxide decorated graphene/carbon nanotube sulfur composite with high sulfur content (81.8 wt%) delivers a high initial specific capacity of 1015.1 mA h g −1 at a current density of 0.1C, high coulombic efficiency approaching 100% and high capacity retention of 84.1% after 100 cycles. The nanocomposites developed in this work have promising applications in high-performance lithium–sulfur batteries.